The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1161/hh0202.104923
|View full text |Cite
|
Sign up to set email alerts
|

Early Expression of Myocardial HIF-1α in Response to Mechanical Stresses

Abstract: Abstract-Vascular endothelial growth factor (VEGF) expression is upregulated by hypoxia-inducible factor-1 (HIF-1) in ischemic tissues and growing tumors. Normally, HIF-1 activity depends on the amount of HIF-1␣ subunit, which is tightly regulated by the oxygen tension. In the myocardium, VEGF expression has been shown to be induced under nonhypoxic conditions by mechanical stresses. However, the cellular mechanism of stress-mediated VEGF induction remains unclear. Therefore, we examined the possible involveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(43 citation statements)
references
References 38 publications
(39 reference statements)
5
38
0
Order By: Relevance
“…Hence, when the bladder depletes the energy reserves during the voiding phase, detrusor contraction fails prematurely and the result is a PVR. Also, it is known that HIF-1α in hypoxic tissues regulates the expression of all enzymes in the glycolytic pathway [20][21][22][23][24]. These observations are consistent with the present study, where high expression of HIF-1α was four times more likely in men with UR.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Hence, when the bladder depletes the energy reserves during the voiding phase, detrusor contraction fails prematurely and the result is a PVR. Also, it is known that HIF-1α in hypoxic tissues regulates the expression of all enzymes in the glycolytic pathway [20][21][22][23][24]. These observations are consistent with the present study, where high expression of HIF-1α was four times more likely in men with UR.…”
Section: Discussionsupporting
confidence: 93%
“…The first subunit is almost undetectable under normal oxygen tension because it is rapidly degraded, while the HIF-1 β subunit is constitutively expressed and controlled in an oxygen-independent manner [21]. HIF-1 α can also be stimulated by other cytokines in normoxic conditions [22], but it can also be activated in response to mechanical stress [23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, under normoxic conditions, the expression and activity of HIF-1α and the subsequent secreted angiogenic factors in cancer can be abnormally up-regulated by different signaling pathways [34], [35], [36] involving Akt and its downstream effectors [20], [22]. Therefore, we hypothesized that RBP2 regulates HIF-1α through the activation of Akt signaling, and we further sought to detect the signaling mechanisms involved in RBP2-mediated tumor angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Another study demonstrated that RBP2 up-regulates the expression of N-cadherin and snail via the activation of Akt signaling [18]. Moreover, ITGB1 and Akt signaling are significantly correlated with tumor angiogenesis [19], [20], [21], [22]. Taken together, these results suggest an oncogenic role for RBP2 in tumor angiogenesis and progression.…”
Section: Introductionmentioning
confidence: 86%
“…From a scientific standpoint, this validates our belief that concentrating on late reperfusion events, rather than early ischaemic injury, represents a logical approach to modulating infarct development. For example, VEGF production being under transcriptional control requires hours to develop [28], and therefore VEGF-mediated oedema represents a reasonable interventional target for I/R injury. The same is true for the numerous oedema and inflammatory mediators (such as PAF, cytokines and eicosanoids) generated by activated leucocytes during reperfusion.…”
Section: Infarct Area (% Ischaemicmentioning
confidence: 99%